Case study to determine the camber of post- tensioned 'I' beam - Lee, Poh Huat (2005)
A common problem that most contractors faced in beam bridge construction was to predict the actual camber of pre-tensioned or post-tensioned beams due to prestressing in order to achieve bridge design finished levels without any unforeseen additional construction cost. Four numbers of full scale 36m long post-tensioned â€œIâ€ beam with overall height of 1.98m was used to measure the actual beam camber on site by means of checking the differences of beamâ€™s top levels while design estimation carried out is based on design code of practice for structural use of concrete BS 8110 by taken into consideration initial prestress losses due to friction and anchorage draw-in of tendons. Comparison between these two methods of evaluation reveals a significant difference. The results shows actual beam cambers measured on site are much larger compare to design prediction. The immediate camber occurred after prestressing is greater by 10.8% and continue to increase to 54.5% over 15 days with a sharp increase focused on the first 3 days after prestressing. From the findings, itâ€™s therefore concluded that deflection of posttensioned beam cannot be predicted accurately due to many field factors which may possibly influence loss of prestress force in post-tensioned cables and behaviour of beam cambering process. However, design calculation can be used as an approximate estimation or as a guide for construction purposes Case study to determine the camber of post- tensioned 'I' beam.